On a highway to the brain: A review on nose-to-brain drug delivery using nanoparticles - Formica, María L.; Real, Daniel A.; Picchio, Matías L.; Catlin, Elise; Donnelly, Ryan F.; Paredes, Alejandro J. (Applied materials today, 2022)
•The difficulty in the treatment of several diseases which affect the central nervous system (CNS) is related to the low permeation of therapeutic agents across the blood-brain barrier.•With unique anatomical features, the intranasal route allows direct entry to the CNS mainly through the sensory neuronal pathway or indirectly by passage across the BBB from the systemic circulation.•Nanoparticles administered via this route can provide drug accumulation in the CNS.•This review focuses on the intranasal delivery of polymer, lipid, and inorganic nanoparticles and drug nanocrystals to treat diseases that affect millions of people globally. The administration of drugs to the central nervous system (CNS) is primarily controlled by the blood-brain barrier (BBB), a structure that prevents the passage of foreign compounds from the blood to the brain's extracellular fluid. Although currently available treatments for brain diseases that affect millions of people globally are partially effective, they are associated with severe side effects of systemic drug distribution. On the other hand, the ability of certain drugs to permeate through the BBB is impeded by their physicochemical properties, achieving sub-therapeutic concentrations in their target tissues. In this sense, the intranasal route with its unique anatomical features provides a promising passage for the delivery of drugs to the brain. Nanoparticle-based systems, in particular, have demonstrated an outstanding capacity to overcome the challenges presented by the intranasal route and produce drug accumulation in the brain while avoiding systemic distribution. This review covers recent developments in the use of polymer, lipid, and inorganic nanoparticles, as well as drug nanocrystals, to deliver drugs to the brain via intranasal administration. A general discussion including favourable aspects and limitations of this approach is also provided. [Display omitted]